Endoscopic Submucosal Dissection vs. Surgery for Superficial Esophageal Squamous Cancer: A Systematic Review and Meta-Analysis - Liu, Zhifeng; Zhao, Renping (Frontiers in Oncology, 2022)
Background: Esophageal cancer is one of the leading causes of morbidity and mortality across the world. Only one systematic review and meta-analysis has attempted to compare the morbidity and mortality outcomes in superficial esophageal squamous cancer patients undergoing endoscopic submucosal dissection (ESD) and esophagectomy (ESO), however, with several limitations. This study aimed to compare the outcomes of hospital stay duration, procedure duration, recurrence, complications, all-cause mortality, short-term survival, and long-term survival in patients with superficial esophageal squamous cancer undergoing ESD and ESO. Methods: Six databases (Web of Science, PubMed, EMBASE, CENTRAL, Scopus, and MEDLINE) were systematically searched according to PRISMA guidelines for eligible studies. With the available literature, we conducted a random-effect meta-analysis to evaluate weighted effects size and odds ratios to determine the comparative morbidity and mortality outcomes between patients with superficial esophageal squamous cancer undergoing ESD and ESO. Results: We found 16 eligible studies detailing 5213 and 8049 age and sex-matched patients undergoing ESD and ESO, respectively. Meta-analysis revealed reduced hospital stay (Hedge’s g: -1.22) and procedure duration (g: -4.54) for patients undergoing ESD. We also observed significantly reduced risks for complications (odds ratio: 0.35), and all-cause mortality (OR: 0.56) in patients undergoing ESD. Differences in recurrence (OR: 0.95), short-term (OR: 1.10), and long-term survival (OR: 0.81) outcomes were not significantly different between ESD and ESO. Conclusions: This meta-analysis provides evidence concerning the improved morbidity and mortality outcomes in superficial esophageal squamous cancer patients undergoing ESD as compared to ESO. The findings herein may aid in developing clinical awareness and assisting best practice guideline development for managing superficial esophageal squamous cancer.